Positive electrode slurry, homogenizing method thereof and lithium ion battery
By adding zero-dimensional and one-dimensional conductive agent in step by step, combining glue liquid with negative pressure state and specific process control, the problem of poor viscosity increase and dispersion effect in the positive electrode slurry homogenization of lithium-ion battery is solved, and the uniformity of slurry is improved and conductivity, optimize battery performance.
Patent Information
- Application Number
- CN202411342955.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-14
AI Technical Summary
In the existing lithium-ion battery positive electrode slurry homogenization process, the viscosity rises too quickly and leads to particle agglomeration, low solid content, and poor dispersion effect of conductive agent, which affects the battery's electrical performance.
The zero-dimensional conductive agent and one-dimensional conductive agent are added in step by step to form a conductive network, combining the glue liquid to ensure the uniformity and stability of the slurry, avoiding the rapid increase in viscosity, and controlling the slurry using the negative pressure state and specific stirring speed and temperature. preparation of material.
The uniformity and stability of the positive electrode slurry are improved, the conductivity is enhanced, the electrode resistance is reduced, the battery polarization is reduced, and the coating performance is optimized.
Smart Images

Figure CN119303462A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a positive electrode slurry and a homogenization method thereof and a lithium ion battery. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, high voltage, high cycle and high operating temperature, and are widely used. The preparation process of lithium-ion batteries includes homogenization, coating, rolling, slitting, baking, assembly, injection, formation and other processes. Among them, homogenization is the first process in the preparation of lithium-ion batteries. It is the process of dissolving, mixing and reacting materials from powder to high-viscosity and high-density materials. The dispersion effect of the slurry directly affects the coating effect. It can be seen that the homogenization process is extremely important.
[0003] At present, there are two kinds of positive electrode slurry homogenization processes for lithium-ion batteries. The first wet process is to first stir the solvent and the binder, then add the conductive agent and stir, and then add the active material and stir to prepare the positive electrode slurry. This process takes a very long time to prepare, which seriously affects the production efficiency. In addition, the viscosity will rise too quickly during the stirring process, causing particle agglomeration. The slurry has a low solid content, which easily leads to poor stability of the slurry. The slurry is easy to stratify after being placed for a period of time. The second dry process is to first put the binder, conductive agent, and active material into a homogenizer for dry mixing, and then add the solvent to stir to prepare the positive electrode slurry. In this process, since the binder is not easy to dissolve when the solvent is added after dry mixing, it is difficult to disperse the slurry, the dispersion effect is poor, and the uniformity of the slurry is affected.
[0004] When using the traditional homogenization process, the viscosity will rise too quickly during the stirring process, causing particles to agglomerate, resulting in a low solid content in the final slurry, or even network clogging, resulting in poor homogenization effect and affecting the electrical performance of the battery. Summary of the invention
[0005] In order to solve the above-mentioned problems in the prior art, an object of the present invention is to provide a positive electrode slurry and a slurrying method thereof and a lithium ion battery, so as to improve the uniformity of the positive electrode slurry.
[0006] The present invention provides a method for homogenizing a positive electrode slurry, the method comprising the following steps:
[0007] S1. Mixing a solvent, a first conductive agent and a dispersant to prepare a slurry A;
[0008] S2. The positive electrode active material and the slurry A are mixed to obtain slurry B;
[0009] S3. mixing the second conductive agent with the slurry B to obtain slurry C;
[0010] S4. The slurry C is mixed with the glue to obtain a positive electrode slurry;
[0011] The first conductive agent includes a zero-dimensional conductive agent, the second conductive agent includes a one-dimensional conductive agent, and the glue includes a binder.
[0012] Since the conductive agent and the positive electrode active material are directly added to the prepared glue solution, the positive electrode active material cannot be well infiltrated in the formed positive electrode slurry, and the particles are easily agglomerated, resulting in too fast generation, so that the final slurry solid content is low, and even the network blocking phenomenon occurs; and the conductive agent cannot form a good conductive network, which affects the electrical performance of the battery. On the one hand, in the last step 5, the glue solution is mixed with the slurry C to prepare the positive electrode slurry. No glue solution is added in the preparation of slurry A, slurry B and slurry C. Instead, the conductive agent, dispersant and positive electrode active material are prepared to obtain the corresponding slurry C before mixing with the glue solution, so that the viscosity of the slurry C containing the conductive agent, dispersant and positive electrode active material will not rise too fast in the process of preparing the positive electrode slurry, causing particle agglomeration. On the other hand, the first conductive agent, a zero-dimensional conductive agent, and the second conductive agent, a one-dimensional conductive agent, of the present invention are added in step S2 and step S4, respectively. In the preparation of slurry A, the slurry A prepared using the zero-dimensional conductive agent and the dispersant has a good dispersion effect in the slurry A because the zero-dimensional conductive agent is in a granular form, and the point-shaped (granular) zero-dimensional conductive agent is also easier to be evenly distributed between the particles of the positive electrode active material when the positive electrode active material is subsequently added; the second conductive agent includes a one-dimensional conductive agent. After the positive electrode active material is mixed with the first conductive agent (zero-dimensional conductive agent), the one-dimensional conductive agent is added. Due to the fibrous structure of the one-dimensional conductive agent, the fibrous conductive agent The contact forms with the positive electrode active material include point contact and point-line contact. The fibrous structure can ensure the improvement of the conductivity between the positive electrode active materials and in the horizontal and vertical directions, greatly improving the conductivity of the electrode, and can make the second conductive agent (one-dimensional conductive agent) and the first conductive agent (zero-dimensional conductive agent) disperse more evenly between the positive electrode active material particles. When subsequently coated for the preparation of the positive electrode sheet, the first conductive agent and the second conductive agent form a large number of uniform conductive contact sites between the positive electrode active material particles, forming a good conductive network, reducing the contact impedance between the positive electrode active material particles, thereby reducing the resistance of the positive electrode sheet and reducing the battery polarization. The above processes work synergistically, so that the positive electrode slurry prepared by the homogenization method of the present invention is uniform, stable, and has an appropriate solid content.
[0013] Preferably, the mass ratio of the first conductive agent to the second conductive agent is 1.8 to 1.0.
[0014] In this scheme, the mass ratio of the first conductive agent to the second conductive agent is 1.8 to 1.0. The mass ratio of the two conductive agents within this range can not only increase the contact between the conductive agent and the positive electrode active material, greatly improve the conductivity of the electrode, but also make the second conductive agent (one-dimensional conductive agent) and the first conductive agent (zero-dimensional conductive agent) more evenly dispersed between the positive electrode active material particles. When subsequently coated for preparing the positive electrode, the first conductive agent and the second conductive agent form a large number of uniform conductive contact sites between the positive electrode active material particles, forming a good conductive network.
[0015] Preferably, when the temperature is 20-45° C., the viscosity of the glue is 3000-9000 mPa·s.
[0016] In this solution, when the temperature is 20-45°C, the viscosity of the glue is 3000-9000 mPa·s, which can further prevent the viscosity of the slurry C containing the conductive agent, the dispersant and the positive electrode active material from rising too fast during the preparation of the positive electrode slurry, thereby causing particle agglomeration, and the glue can be evenly dispersed in the system of the slurry C, thereby improving the bonding performance of the positive electrode active material and the conductive agent, enhancing the interaction between the positive electrode active material and the conductive agent, and reducing the resistance of the positive electrode sheet.
[0017] Preferably, the mixing process involved in S1 to S4 includes: the stirring line speed of S1 to S4 is 15-20 m / min, the dispersion line speed of S1 to S2 is 8-12 m / min, the dispersion line speed of S3 to S4 is 40-60 m / min, and the temperature is not more than 45°C.
[0018] More preferably, the mixing temperature in S1 to S4 is not less than 25°C and not more than 45°C.
[0019] Preferably, the preparation method of the glue solution includes: the temperature during the preparation process is not more than 45°C, first stirring and dispersing at a low speed, and then stirring and dispersing at a high speed; the low-speed stirring and dispersing is: the stirring line speed is 7 to 12 m / min, and the dispersing line speed is 18 to 20 m / min; the high-speed stirring and dispersing is: the stirring line speed is 12 to 17 m / min, and the dispersing line speed is 40 to 60 m / min.
[0020] The method for preparing the adhesive into a glue liquid in this scheme includes: the temperature during the preparation process is not greater than 45°C, first stirring and dispersing at a low speed, and then stirring and dispersing at a high speed, which can make the prepared glue liquid uniform and improve the stability of the glue liquid.
[0021] Preferably, in step S3, D50 of the positive electrode active material is 0.3-1.5 μm, and the carbon content of the positive electrode active material is 1.6%wt-2.3%wt.
[0022] In step S3 of this scheme, the D50 of the positive electrode active material is 0.3-1.5 μm, and the carbon content of the positive electrode active material is 1.6% wt-2.3% wt. For positive electrode active materials with smaller particle size and higher carbon content, the positive electrode slurry homogenization method of this scheme is used to improve the uniformity and stability of the positive electrode slurry and the fineness of the positive electrode slurry.
[0023] Preferably, the zero-dimensional conductive agent includes at least one of an SP conductive agent, an AB (acetylene black) conductive agent, and Ketjen black.
[0024] Preferably, the one-dimensional conductive agent includes at least one of a CNT conductive agent and a VGCF conductive agent.
[0025] Preferably, the mass ratio of the positive electrode active material: the first conductive agent: the second conductive agent: the binder: the dispersant is (95%-98%): (0.3%-0.7%): (0.2%-0.6%): (1.5%-1.9%): (0.1%-0.3%).
[0026] Preferably, the mass ratio of the positive electrode active material: the first conductive agent: the second conductive agent: the binder: the dispersant is 97.2%: 0.5%: 0.4%: 1.7%: 0.2%.
[0027] Preferably, during the processes of S3 and S4, the homogenization system is maintained in a negative pressure state, and the vacuum degree of the negative pressure state is not greater than 0.085 MPa.
[0028] In the process of S3 and S4, the present solution maintains the homogenization system in a negative pressure state, and the vacuum degree of the negative pressure state is not greater than 0.085 MPa, which can effectively remove bubbles from the slurry without excessively degassing the slurry and reducing the product quality.
[0029] Preferably, in S4, when the temperature is not greater than 45°C, the viscosity of the positive electrode slurry is 6000 to 23000 mPa·s.
[0030] In the present solution, in S4, when the temperature is not greater than 45° C., the viscosity of the positive electrode slurry is 6000 to 23000 mPa·s. Adjusting the slurry viscosity within this range can not only maintain a suitable solid content of the slurry, but also facilitate the construction of the subsequent coating process.
[0031] The present invention provides a positive electrode slurry, wherein the positive electrode slurry is prepared by a homogenization method of the positive electrode slurry.
[0032] The present invention also provides a lithium ion battery, which comprises the positive electrode slurry. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The graph of the viscosity change of the positive electrode slurry prepared in Example 1 and Comparative Example 1 within 24 hours. DETAILED DESCRIPTION
[0034] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments.
[0035] Example 1
[0036] S1. Preparation of adhesive solution: 69.6 g of PVDF (polyvinylidene fluoride) and 800.4 g of NMP (N-methylpyrrolidone) were added into a stirring tank at the same time, and the tank body was kept in a negative pressure state (vacuum degree was 0.06 MPa). The linear speed of the stirring paddle was 10 m / min, the linear speed of the dispersing paddle was 20 m / min, and the stirring paddle and the dispersing paddle were operated simultaneously, and stirring and dispersing were performed for 40 minutes; after the binder was initially dissolved, the linear speed of the stirring paddle was 15 m / min, the linear speed of the dispersing paddle was 50 m / min, and the stirring paddle and the dispersing paddle were operated simultaneously, and stirring and dispersing were performed for 80 minutes to obtain an adhesive solution (viscosity was 6500 mPa·s).
[0037] S2. 1.45 kg of NMP, 21 g of conductive carbon black SP, and 11 g of dispersant (YTF003 dispersant from Shenzhen Yite Technology Co., Ltd.) were added into a stirring tank. The linear speed of the stirring paddle was 20 m / min, and the linear speed of the dispersing paddle was 8 m / min. The stirring paddle and the dispersing paddle were operated simultaneously. Stirring and dispersing were performed for 20 min to obtain slurry A.
[0038] S3. Add 4 kg of carbon-coated LMFP (carbon-coated lithium manganese iron phosphate, D50 is 0.7 μm, carbon content is 1.8 wt%) as the main material into the slurry A obtained in step S2, with the stirring paddle linear speed of 20 m / min, the dispersing paddle linear speed of 8 m / min, the stirring paddle and the dispersing paddle working simultaneously, stirring and dispersing for 20 min, so that the carbon-coated LMFP main powder is fully infiltrated into a thick muddy slurry, and use a scraper to scrape the cylinder to scrape off the thick muddy slurry remaining on the stirring paddle, the dispersing paddle and the cylinder wall, with the stirring paddle linear speed of 20 m / min, the dispersing paddle linear speed of 50 m / min, the stirring paddle and the dispersing paddle working simultaneously, stirring and dispersing for 20 min, to obtain slurry B.
[0039] S4. Add 330 g of CNT (carbon nanotube) conductive slurry (solid content is 5 wt%) into the stirring tank of slurry B obtained in step S3, maintain the tank body in a negative pressure state (vacuum degree is 0.06 MPa), the stirring paddle linear speed is 20 m / min, the dispersing paddle linear speed is 50 m / min, the stirring paddle and the dispersing paddle are operated simultaneously, stirring and dispersing for 100 minutes to obtain slurry C.
[0040] S5. Add the glue obtained in step S1 to the stirring tank of slurry C obtained in step S5, keep the tank body in a negative pressure state (vacuum degree is 0.06Mpa), the stirring paddle linear speed is 20m / min, the dispersing paddle linear speed is 50m / min, the stirring paddle and the dispersing paddle are operated simultaneously, and stirring and dispersing are performed for 100min; keep the tank body in a negative pressure state (vacuum degree is 0.06Mpa), add NMP, adjust the slurry viscosity to 12000mPa·s, release the negative pressure condition, and reduce the stirring speed and dispersing speed, the stirring paddle linear speed is 10m / min, the dispersing paddle linear speed is 8m / min, the stirring paddle and the dispersing paddle are operated simultaneously, stirring and dispersing are performed, and the desired LMFP positive electrode slurry is obtained after 1h.
[0041] Example 2
[0042] The homogenization method of the positive electrode slurry in this embodiment is the same as that in Embodiment 1, except that 16.5 g of conductive carbon black SP is used in step S2 and 420 g of CNT (carbon nanotube) conductive slurry (solid content is 5 wt%) is used in step S4.
[0043] Example 3
[0044] The homogenization method of the positive electrode slurry in this embodiment is the same as that in Embodiment 1, except that 25 g of conductive carbon black SP is used in step S2 and 250 g of CNT (carbon nanotube) conductive slurry (solid content is 5 wt%) is used in step S4.
[0045] Example 4
[0046] The viscosity of the glue prepared in step S1 of the slurrying method of the positive electrode slurry in this embodiment is 2600mPa·s. The specific preparation method of the glue is: 69.6g of PVDF (polyvinylidene fluoride) and 800.4g of NMP (N-methylpyrrolidone) are added to the stirring tank at the same time, and the negative pressure state (vacuum degree is 0.06Mpa) is maintained. The stirring paddle linear speed is 10m / min, the dispersing paddle linear speed is 20m / min, the stirring paddle and the dispersing paddle are operated simultaneously, and stirring and dispersing are performed for 40min; after the binder is initially dissolved, the stirring paddle linear speed is 20m / min, the dispersing paddle linear speed is 80m / min, the stirring paddle and the dispersing paddle are operated simultaneously, and stirring and dispersing are performed for 120min.
[0047] The rest is the same as steps S2 to S5 of Example 1.
[0048] Example 5
[0049] The viscosity of the glue prepared in step S1 of the slurrying method of the positive electrode slurry in this embodiment is 10600mPa·s. The specific preparation method of the glue is: 69.6g of PVDF (polyvinylidene fluoride) and 800.4g of NMP (N-methylpyrrolidone) are added to the stirring tank at the same time, and the negative pressure state (vacuum degree is 0.06Mpa) is maintained. The stirring paddle linear speed is 10m / min, the dispersing paddle linear speed is 15m / min, the stirring paddle and the dispersing paddle are operated simultaneously, and stirring and dispersing are performed for 40min; after the binder is initially dissolved, the stirring paddle linear speed is 10m / min, the dispersing paddle linear speed is 30m / min, the stirring paddle and the dispersing paddle are operated simultaneously, and stirring and dispersing are performed for 120min.
[0050] The rest is the same as steps S2 to S5 of Example 1.
[0051] Example 6
[0052] The homogenization method of the positive electrode slurry in this embodiment is the same as that in Embodiment 1 except that the carbon-coated lithium manganese iron phosphate having a D50 of 0.2 μm is used in step S3.
[0053] Example 7
[0054] The positive electrode slurry homogenization method of this embodiment is the same as that of Embodiment 1, except that the vacuum degree of the cylinder in the negative pressure state in step S1, step S4 and step S5 is maintained at 0.1 MPa, the conductive carbon black SP used in step S2 is replaced by AB (acetylene black) conductive agent, and the CNT (carbon nanotube) conductive slurry (solid content of 5 wt%) used in step S4 is replaced by VGCF conductive agent slurry (solid content of 5 wt%).
[0055] Example 8
[0056] The homogenization method of the positive electrode slurry in this embodiment is the same as that in Embodiment 1 except that step S5 adjusts the slurry viscosity to 4000 mPa·s.
[0057] Example 9
[0058] The homogenization method of the positive electrode slurry in this embodiment is the same as that in Embodiment 1 except that step S5 adjusts the slurry viscosity to 28000 mPa·s.
[0059] Comparative Example 1
[0060] S1. Preparation of adhesive solution: 69.6 g of PVDF (polyvinylidene fluoride) and 800.4 g of NMP (N-methylpyrrolidone) were added into a stirring tank at the same time, and the tank body was kept in a negative pressure state (vacuum degree was 0.06 MPa). The linear speed of the stirring paddle was 10 m / min, the linear speed of the dispersing paddle was 20 m / min, and the stirring paddle and the dispersing paddle were operated simultaneously, and stirring and dispersing were performed for 40 minutes; after the binder was initially dissolved, the linear speed of the stirring paddle was 15 m / min, the linear speed of the dispersing paddle was 50 m / min, and the stirring paddle and the dispersing paddle were operated simultaneously, and stirring and dispersing were performed for 80 minutes to obtain an adhesive solution (viscosity was 6500 mPa·s).
[0061] S2. Add 1.45 kg of NMP, 21 g of conductive carbon black SP, 330 g of CNT (carbon nanotube) conductive slurry (solid content of 5 wt%), and 11 g of dispersant (YTF003 dispersant from Shenzhen Yite Technology Co., Ltd.) into the glue obtained in step S1. The cylinder body is kept in a negative pressure state (vacuum degree is 0.06 MPa), the linear speed of the stirring paddle is 20 m / min, the linear speed of the dispersing paddle is 50 m / min, the stirring paddle and the dispersing paddle are operated simultaneously, stirring and dispersing are carried out for 100 minutes, and the cylinder body is kept in a negative pressure state (vacuum degree is 0.06 MPa) to obtain slurry A.
[0062] S3. Add 4 kg of carbon-coated LMFP (carbon-coated lithium manganese iron phosphate, D50 is 0.7 μm, carbon content is 1.8 wt%) as the main material to the slurry A prepared in step S2, and maintain the cylinder in a negative pressure state (vacuum degree is 0.06 MPa), the stirring paddle linear speed is 20 m / min, the dispersing paddle linear speed is 50 m / min, the stirring paddle and the dispersing paddle are operated simultaneously, and stirring and dispersing are performed for 100 min; the cylinder is maintained in a negative pressure state (vacuum degree is 0.06 MPa) and NMP is added to adjust the slurry viscosity to 12000 mPa·s, the cylinder is maintained in a negative pressure state (vacuum degree is 0.06 MPa), the negative pressure condition is released, and the stirring speed and dispersing speed are reduced. The stirring paddle linear speed is 10 m / min, the dispersing paddle linear speed is 8 m / min, the stirring paddle and the dispersing paddle are operated simultaneously, stirring and dispersing are performed, and the desired LMFP positive electrode slurry is obtained after 1 hour.
[0063] Comparative Example 2
[0064] The homogenization method of the positive electrode slurry in this comparative example is the same as that in Example 1, except that 16.5 g of conductive carbon black SP is used in step S4 to replace 330 g of CNT (carbon nanotube) conductive slurry (solid content is 5 wt%).
[0065] Comparative Example 3
[0066] The homogenization method of the positive electrode slurry in this comparative example is the same as that in Example 1, except that 420 g of CNT (carbon nanotube) conductive slurry (solid content of 5 wt%) is used in step S2 to replace 21 g of conductive carbon black SP.
[0067] Comparative Example 4
[0068] S1. Preparation of adhesive solution: 69.6 g of PVDF (polyvinylidene fluoride) and 800.4 g of NMP (N-methylpyrrolidone) were added into a stirring tank at the same time, and the tank body was kept in a negative pressure state (vacuum degree was 0.06 MPa). The linear speed of the stirring paddle was 10 m / min, the linear speed of the dispersing paddle was 20 m / min, and the stirring paddle and the dispersing paddle were operated simultaneously, and stirring and dispersing were performed for 40 minutes; after the binder was initially dissolved, the linear speed of the stirring paddle was 15 m / min, the linear speed of the dispersing paddle was 50 m / min, and the stirring paddle and the dispersing paddle were operated simultaneously, and stirring and dispersing were performed for 80 minutes to obtain an adhesive solution (viscosity was 6500 mPa·s).
[0069] S2. 1.45 kg of NMP, 21 g of conductive carbon black SP, 330 g of CNT (carbon nanotube) conductive slurry (solid content of 5 wt%), and 11 g of dispersant (YTF003 dispersant from Shenzhen Yite Technology Co., Ltd.) were added into a stirring tank. The tank body was kept in a negative pressure state (vacuum degree was 0.06 MPa). The linear speed of the stirring paddle was 20 m / min, and the linear speed of the dispersing paddle was 50 m / min. The stirring paddle and the dispersing paddle were operated simultaneously. Stirring and dispersing were performed for 100 minutes. The tank body was kept in a negative pressure state (vacuum degree was 0.06 MPa) to obtain slurry A.
[0070] S3. Add 4 kg of carbon-coated LMFP (carbon-coated lithium manganese iron phosphate, D50 is 0.7 μm, carbon content is 1.8 wt%) as the main material to the slurry A obtained in step S2, maintain the cylinder in a negative pressure state (vacuum degree is 0.06 MPa), the stirring paddle linear speed is 20 m / min, the dispersing paddle linear speed is 50 m / min, the stirring paddle and the dispersing paddle are operated simultaneously, stirring and dispersing are performed for 100 minutes, and the cylinder is maintained in a negative pressure state (vacuum degree is 0.06 MPa) to obtain slurry B.
[0071] S4. Add the glue obtained in step S1 to the stirring tank of slurry B obtained in step S3, maintain the cylinder body in a negative pressure state (vacuum degree is 0.06Mpa), the linear speed of the stirring paddle is 20m / min, the linear speed of the dispersing paddle is 50m / min, the stirring paddle and the dispersing paddle are operated simultaneously, stirring and dispersing for 100min, the cylinder body is maintained in a negative pressure state (vacuum degree is 0.06Mpa), add NMP, adjust the slurry viscosity to 12000mPa·s, maintain the cylinder body in a negative pressure state (vacuum degree is 0.06Mpa), release the negative pressure condition, and reduce the stirring speed and dispersing speed, the linear speed of the stirring paddle is 10m / min, the linear speed of the dispersing paddle is 8m / min, the stirring paddle and the dispersing paddle are operated simultaneously, stirring and dispersing, and the desired LMFP positive electrode slurry is obtained after 1h.
[0072] Comparative Example 5
[0073] S1. Add 69.6g of PVDF (polyvinylidene fluoride) and 800.4g of NMP (N-methylpyrrolidone) into a stirring tank at the same time, keep the tank in a negative pressure state (vacuum degree is 0.06Mpa), the stirring paddle linear speed is 10m / min, the dispersing paddle linear speed is 20m / min, the stirring paddle and the dispersing paddle are operated simultaneously, and stirring and dispersing are carried out for 40min; after the binder is initially dissolved, the stirring paddle linear speed is 15m / min, the dispersing paddle linear speed is 50m / min, the stirring paddle and the dispersing paddle are operated simultaneously, and stirring and dispersing are carried out for 80min to obtain a glue solution (viscosity is 6500mPa·s).
[0074] S2. Add 1.45 kg of NMP, 21 g of conductive carbon black SP, and 11 g of dispersant (YTF003 dispersant from Shenzhen Yite Technology Co., Ltd.) to the rubber solution prepared in step S1, and add them into a stirring tank. The tank body is kept in a negative pressure state (vacuum degree is 0.06 MPa), the linear speed of the stirring paddle is 20 m / min, the linear speed of the dispersing paddle is 8 m / min, the stirring paddle and the dispersing paddle are operated simultaneously, and stirring and dispersing are performed for 20 minutes to obtain slurry A.
[0075] S3. Add 4 kg of carbon-coated LMFP (carbon-coated lithium manganese iron phosphate, D50 is 0.7 μm, carbon content is 1.8 wt%) as the main material to the slurry A prepared in step S2, maintain the cylinder in a negative pressure state (vacuum degree is 0.06 MPa), the stirring paddle linear speed is 20 m / min, the dispersing paddle linear speed is 8 m / min, the stirring paddle and the dispersing paddle are operated simultaneously, stirring and dispersing for 20 minutes, so that the carbon-coated LMFP main powder is fully infiltrated into a thick muddy slurry, use a scraper to scrape the cylinder, and scrape off the thick muddy slurry remaining on the stirring paddle, the dispersing paddle and the cylinder wall, the stirring paddle linear speed is 20 m / min, the dispersing paddle linear speed is 50 m / min, the stirring paddle and the dispersing paddle are operated simultaneously, stirring and dispersing for 20 minutes, and obtain slurry B.
[0076] S4. Add 330g of CNT (carbon nanotube) conductive slurry (solid content of 5wt%) into the stirring tank of slurry B obtained in step S3, keep the cylinder in a negative pressure state (vacuum degree of 0.06Mpa), the linear speed of the stirring paddle is 20m / min, the linear speed of the dispersing paddle is 50m / min, the stirring paddle and the dispersing paddle are operated simultaneously, stirring and dispersing for 100min, keep the cylinder in a negative pressure state (vacuum degree of 0.06Mpa), add NMP, adjust the slurry viscosity to 12000mPa·s, release the negative pressure condition, and reduce the stirring speed and dispersing speed, the linear speed of the stirring paddle is 10m / min, the linear speed of the dispersing paddle is 8m / min, the stirring paddle and the dispersing paddle are operated simultaneously, stirring and dispersing, and the desired LMFP positive electrode slurry is obtained after 1h.
[0077] Performance Testing
[0078] 1. Slurry performance
[0079] Solid content test method: Take an appropriate amount of slurry and put it into a high temperature resistant container and weigh it, then put the container into a high temperature heating oven until the solvent evaporates completely (120℃ for about 3h), and weigh the remaining dry material mass. Solid content = dry material mass / slurry mass.
[0080] Fineness test method: Take about 5mL of slurry and drop it on the fineness scraper, then use the scraper to scrape from top to bottom. The reading corresponding to the place where the scratch first appears is the slurry fineness.
[0081] Sedimentation test method: After the slurry is stirred, take equal mass of slurry in a beaker, take the upper slurry to test the solid content C1; then leave it at room temperature for 24 hours, take the bottom slurry in the beaker, and test the solid content C2. The value of C1-C2 is the 24-hour slurry sedimentation.
[0082] Preparation of positive electrode
[0083] The positive electrode slurry prepared in the above embodiments and comparative examples was coated on the surface of the current collector (aluminum foil) at a coating speed of 10 m / s, an oven temperature of 105±5°C, and an oven wind speed of 4 m / s to obtain a positive electrode sheet.
[0084] 2. Pole performance
[0085] Pole piece peeling force: Use a lithium battery peeling force tester to cut the positive electrode piece into 50*200mm strips, fix one end to the surface of the stretching area with double-sided tape, and fix the other end with the clamp that comes with the equipment. Start the machine at a speed of 100mm / min to measure the peeling force of the electrode piece.
[0086] Electrode piece resistance: The double-probe method is used to test the electrode piece resistance. The electrode piece is cut into a circular size with a diameter of about 12mm, and then placed between the two probes. The two probes are connected to the resistance meter through two poles. The handle of the test device is turned to squeeze the electrode piece with a stable pressure. The pressure is controlled by the pressure gauge. When the pressure requirement is reached, the resistance data of the resistance meter is read. This data is the relative value of the electrode piece resistance.
[0087] The test results are shown in Table 1:
[0088] Table 1
[0089]
[0090]
[0091] From the analysis of Table 1, we can see that:
[0092] Compared with Example 1, Example 2 uses less first conductive agent zero-dimensional conductive agent conductive carbon black SP, Example 3 uses less second conductive agent one-dimensional conductive agent CNT, and the ratio of zero-dimensional conductive agent and one-dimensional conductive agent used in Example 2 and Example 3 is not in the preferred range of 1.8 to 1.0. From the test results in Table 1, it can be seen that compared with Example 1, the pole sheet resistance of the pole sheet prepared by the homogenization method in Example 2 and Example 3 is increased, which shows that the ratio of zero-dimensional conductive agent and one-dimensional conductive agent is in the preferred range of 1.8 to 1.0, which can further reduce the resistance of the pole sheet and reduce battery polarization.
[0093] Compared with Example 1, the viscosity of the glue in Example 4 and Example 5 is smaller and larger, respectively, and is not within the further preferred glue viscosity range of 3000 to 9000 mPs·s. The glue viscosity in Example 4 is smaller. From the test results in Table 1, it can be seen that compared with Example 1, the 24h solid content sedimentation of the positive electrode slurry prepared by the homogenization method in Example 4 is increased, and the electrode peeling force is reduced. This shows that the viscosity of the glue in the homogenization method is smaller, the uniformity and stability of the prepared positive electrode slurry are all reduced, and thus the performance of the electrode prepared is also reduced. The viscosity of the glue in Example 5 is relatively large. From the test results in Table 1, it can be seen that compared with Example 1, the fineness of the positive electrode slurry prepared by the homogenization method in Example 5 is increased, the 24h solid content sedimentation is increased, and the electrode sheet peeling force is reduced. This shows that the viscosity of the glue is relatively large, which makes the viscosity of the slurry containing the conductive agent, dispersant and positive electrode active material increase rapidly during the preparation of the positive electrode slurry, resulting in a decrease in the uniformity of the particle distribution in the slurry, and the fineness of the prepared slurry is increased, thereby reducing the peeling force of the prepared electrode.
[0094] Compared with Example 1, the D50 of the carbon-coated lithium manganese iron phosphate used in Example 6 is 0.2 μm, that is, the D50 of the carbon-coated lithium manganese iron phosphate used is smaller, the viscosity will rise faster during the stirring process, the particle agglomeration will increase, the slurry discharge solid content, slurry stability and pole piece peeling force will be affected. From the test results in Table 1, compared with Example 1, the positive electrode slurry prepared in Example 6 has a lower solid content, an increased 24h solid content sedimentation, and a reduced pole piece peeling force. This shows that the use of carbon-coated lithium manganese iron phosphate with a D50 in the range of 0.3 to 1.5 μm can make the prepared positive electrode slurry show good technical effects in terms of slurry performance (discharge solid content, 24h solid content sedimentation) and pole piece performance (pole piece peeling force).
[0095] Compared with Example 1, in Example 7, the vacuum degree of steps S1, S4 and S5 during the homogenization process of the positive electrode slurry is relatively large, resulting in excessive degassing and reduced product quality. The technical effects of the positive electrode slurry prepared in Example 7 in terms of slurry performance (discharge fineness) and electrode sheet performance (electrode sheet resistance) are significantly reduced.
[0096] Compared with Example 1, in Example 8, step S5 adjusts the slurry viscosity to 4000mPa·s during the homogenization of the positive electrode slurry, and in Example 9, step S5 adjusts the slurry viscosity to 28000mPa·s during the homogenization of the positive electrode slurry, which are respectively less than and greater than the preferred adjustment slurry viscosity of 6000-23000mPa·s. In Example 8, step S5 adjusts the slurry viscosity during the homogenization of the positive electrode slurry at a lower level. From the test results in Table 1, the slurry viscosity is adjusted to a lower level, the solid content of the discharge material is reduced, and during coating, the volatilization rate of NMP increases, PVDF floats, and the pole piece peeling force decreases. In Example 9, step S5 adjusts the slurry viscosity to a higher level during the homogenization of the positive electrode slurry. From the test results in Table 1, the slurry fineness increases, the 24h solid content sedimentation increases, and the distribution uniformity of the overall surface density of the pole piece decreases during coating.
[0097] Compared with Example 1, the order of adding materials in the homogenization method of the positive electrode slurry of Comparative Example 1 is: glue + NMP + SP and CNT + positive electrode active material, that is, the order of adding materials in the homogenization method is the wet homogenization process commonly used in the prior art. From the test results in Table 1, compared with Example 1, the technical effects of the positive electrode slurry prepared in Comparative Example 1 in terms of slurry performance (discharge solid content, discharge fineness and 24h solid content sedimentation) and electrode performance (electrode sheet peeling force and electrode sheet resistance) are significantly reduced. This shows that the use of traditional wet homogenization technology for positive electrode active materials with smaller particle size and higher carbon content cannot achieve the technical effects of the prepared positive electrode slurry with better slurry performance and electrode sheet performance.
[0098] Compared with Example 1, Comparative Example 2 does not use only the zero-dimensional conductive agent conductive carbon black SP in the homogenization method, and does not use the one-dimensional conductive agent CNT; Comparative Example 3 uses only the one-dimensional conductive agent CNT in the homogenization method, and does not use the zero-dimensional conductive agent conductive carbon black SP. From the test results in Table 1, when only one of the conductive agents is used, the dispersion uniformity of the conductive agent between the positive electrode active material particles is reduced, and a large number of uniform conductive contact sites cannot be formed between the positive electrode active material particles to form a good conductive network. Therefore, compared with Example 1, the technical effects in terms of 24h solid content sedimentation, electrode peeling force and electrode resistance are significantly reduced.
[0099] Compared with Example 1, during the slurrying method of the positive electrode slurry in Comparative Example 4, the first conductive agent SP and the second conductive agent CNT are added together, that is, they are not added in steps. From the test results in Table 1, compared with Example 1, the technical effects of the positive electrode slurry prepared in Comparative Example 4 in terms of slurry performance (discharge solid content, discharge fineness and 24h solid content sedimentation) and electrode sheet performance (electrode sheet peeling force and electrode sheet resistance) are significantly reduced. This shows that the first conductive agent and the second conductive agent are added step by step according to the addition order in the technical scheme of the present invention, which can achieve the technical effects of the prepared positive electrode slurry with better slurry performance and electrode sheet performance.
[0100] Compared with Example 1, during the homogenization method of the positive electrode slurry of Comparative Example 5, the glue is added in step S2, that is, the conductive agent and the positive electrode active material are directly added to the prepared glue, without first uniformly dispersing the conductive agent and the positive electrode active material, which will cause the viscosity of the formed positive electrode slurry to rise too quickly, causing particle agglomeration, thereby making the final slurry solid content low, and even causing network clogging, resulting in poor homogenization effect. From the test results in Table 1, compared with Example 1, the technical effects of the positive electrode slurry prepared in Comparative Example 5 in terms of slurry performance (discharge solid content, discharge fineness and 24h solid content sedimentation) and electrode performance (electrode peeling force and electrode resistance) are significantly reduced. This shows that the order of adding the glue according to the homogenization method in the technical scheme of the present invention can achieve the technical effects of the prepared positive electrode slurry being superior in both slurry performance and electrode performance.
[0101] Figure 1 The graph of the viscosity change of the positive electrode slurry prepared in Example 1 and Comparative Example 1 in 24 hours. Figure 1 It can be seen that the viscosity change of the positive electrode slurry prepared by the homogenization method in Example 1 within 24 hours is significantly smaller than that in Comparative Example 1. Therefore, it can be explained that the homogenization method of the positive electrode slurry of the present invention can significantly improve the stability of the slurry.
[0102] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for homogenizing a positive electrode slurry, characterized in that: The homogenization method comprises the following steps: S1. Mixing a solvent, a first conductive agent and a dispersant to prepare a slurry A; S2. The positive electrode active material and the slurry A are mixed to obtain slurry B; S3. mixing the second conductive agent with the slurry B to obtain slurry C; S4. The slurry C is mixed with the glue to obtain a positive electrode slurry; The first conductive agent includes a zero-dimensional conductive agent, the second conductive agent includes a one-dimensional conductive agent, and the glue includes a binder.
2. The method for homogenizing the positive electrode slurry according to claim 1, characterized in that: The mass ratio of the first conductive agent to the second conductive agent is 1.8 to 1.
0.
3. The method for homogenizing the positive electrode slurry according to claim 1, characterized in that: When the temperature is 20-45° C., the viscosity of the glue is 3000-9000 mPa·s.
4. The method for homogenizing the positive electrode slurry according to claim 1, characterized in that: The mixing process involved in S1 to S4 includes: the stirring line speed of S1 to S4 is 15 to 20 m / min, the dispersion line speed of S1 to S2 is 8 to 12 m / min, and the dispersion line speed of S3 to S4 is 40 to 60 m / min.
5. The method for homogenizing the positive electrode slurry according to claim 1, characterized in that: The preparation method of the glue solution comprises: first stirring and dispersing at a low speed, and then stirring and dispersing at a high speed; the low-speed stirring and dispersing is: the stirring line speed is 7-12 m / min, and the dispersing line speed is 18-20 m / min; the high-speed stirring and dispersing is: the stirring line speed is 12-17 m / min, and the dispersing line speed is 40-60 m / min.
6. The method for homogenizing positive electrode slurry according to claim 1, characterized in that: The D50 of the positive electrode active material is 0.3-1.5 μm, and the carbon content of the positive electrode active material is 1.6%wt-2.3%wt.
7. The method for homogenizing positive electrode slurry according to claim 1, characterized in that: During the processes of S3 and S4, the homogenization system is kept in a negative pressure state, and the vacuum degree of the negative pressure state is not greater than 0.085 MPa.
8. The method for homogenizing positive electrode slurry according to claim 1, characterized in that: In S4, when the temperature is not greater than 45°C, the viscosity of the positive electrode slurry is 6000-23000 mPa·s.
9. A positive electrode slurry, characterized in that: The positive electrode slurry is prepared by the homogenization method of the positive electrode slurry according to any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode slurry as claimed in claim 9.